127I and 129I species in the English Channel and its adjacent areas: Uncovering impact on the isotopes marine pathways. (15th October 2022) - He, Peng; Pang, Hongying; Yang, Zheng; Li, Sihong; Huang, Yi; Hou, Xiaolin; Possnert, Göran; Zheng, Xuefeng; Pei, Xiangjun; Aldahan, Ala
Highlights: Water masses mixing and dilution control iodine species distribution. A slow reduction of iodate is observed in the western English Channel. Sources of 129 I can be traced by its chemical species. Specific 129 I species fingerprints occur in the estuary and the open ocean. Inventories of 129 I and its species in the English Channel were quantified. Abstract: Radioactive iodine-129 has been released from the La Hague nuclear fuel reprocessing facility (NRF) into the English Channel, but the distribution and transformation of the isotope species, and environmental consequences have not been fully characterized in the Channel. Here we present data on iodine isotopes ( 129 I and 127 I) species in surface water of the English Channel and the southern Celtic Sea. Compared to 127 I species, the concentrations of 129 I − and 129 IO3 − show more variations, but iodate is the major species for both 129 I and 127 I. Our data provide new information regarding iodide-iodate inter-conversion showing that water dilution and mixing are the main factors affecting the 127 I and 129 I species distribution in the Channel. Some reduction of iodate occurs within the English Channel and mainly in the west part because of biotic processes. The 129 I species transformation is overall insignificant, especially in the eastern Channel, where a constant value of 129 IO3 − / 129 I is observed, which might characterize the La Hague wastewater signal. In the Celtic Sea, oxidation of iodide can be traced by 127 I and 129 I species. On a larger scale, 129 I generally experienced an oxidation process in the Atlantic Ocean, while in the coast of shallow shelf seas, new produced 129 I − can be identified, especially in the German Bight and the Baltic Sea. The data of 129 I species in the English Channel can provide estimate of redox rates in a much broader marine areas if the transit time of 129 I from La Hague is well-defined. Furthermore, estimate of inventories for 129 I and its species in the Channel, and fluxes of 129 I species from the English Channel to the North Sea add important information to the geochemical cycle of 129 I. Graphical abstract: Image, graphical abstract